THE BRAZILIAN FEMININE FANTASTIC: A REFLECTION ON FORGOTTEN PRODUCTION (Interdisciplinary Studies Journal, 2025)
The present study aims to reflect on the fantastic production by female authors written between 1850 and 1950, aiming to fill gaps present in Brazilian literary historiography, especially regarding the fantastic narratives of Carmen Dolores, Laura Rosa, and Emília Freitas. Throughout history, female writing has been relegated to an inferior condition. Such relegation is the result of complex historical and social factors that perpetuated gender inequalities. Literature, like many other areas, was predominantly dominated by men, especially in the fantastic genre. Even when women managed to break barriers and write fantastic narratives, these were neglected or erased from literary history. Thus, we seek to bring attention to the fantastic works of the aforementioned authors. To do so, we will use theoretical insights from critics such as Remo Ceserani (2006), Gama-khalil (2013), Rosemary Jackson (1986), Irene Bessière (1974), Julio França (2013), Naiara Araújo (2021), Risolete Hellmann (2015), among others, who approach the fantastic in a nuanced manner, taking into account the variety and complexity of this literary trend.
Keywords: Carmen Dolores; Emília Freitas; Laura Rosa; Fantastic Mode; Female Fantastic Production